Molecular dynamics study of TMPA mediated dissociation of Nur77-LKB1 complex. (October 2018) - Rungsung, Ikrormi; Rajagopalan, Muthukumaran; Ramaswamy, Amutha
Graphical abstract: Highlights: The present study highlights the formation of Nur77-LKB1 complex and the TMPA induced dissociation of Nur77-LKB1 complex using all atom simulation approach. Nur77-LKB1 complex is highly stabilized by several H-bonds formed between the Nur77 residues (Thr567, Gln571, Phe598, and Asp594) and the LKB1 residues (Leu344, Leu344, Glu70, and Arg39), respectively. The strong binding affinity of Nur77 with LKB1 (estimated as –23.58 ± 39.5 kcal/mol) is decreased (to a relatively high energy state having –2.83 ± 20.5 kcal/mol) by the presence of TMPA. TMPA induces an open-closure motion between Nur77 and LKB1 domains which exposes the interfacial regions to the solvent and destabilizes the Nur77-LKB1 complex. Abstract: LKB1 protein is involved in the regulation of cell polarity by phosphorylating the AMPK under energetic stress conditions. LKB1 protein is expressed in both cytoplasm and nucleus. In the nucleus, LKB1 interacts with orphan nuclear receptor protein Nur77. It is reported that the interaction of LKB1 with Nur77 is disrupted by the small molecular ligand TMPA (ethyl 2-[2, 3, 4-trimethoxy-6-(1-octanoyl)phenyl]acetate), such that the LKB1 is enabled to play its role in cytoplasm and further to regulate/reduce the blood glucose level. In the present study, atomistic molecular dynamics simulations are performed to understand the dissociation mechanism of Nur77-LKB1 complex. The present study reveals that TMPAs induce an open-close motion of Nur77 which further decrease the stability of Nur77-LKB1 complex. As a consequence, the interface region in LKB1-Nur77 complex is more exposed for solvation and further releases the interactions existing between Nur77 and LKB1. Altogether, this study explains the TMPAs mediated Nur77-LKB1 complex dissociation.